2010
DOI: 10.1186/1472-6963-10-227
|View full text |Cite
|
Sign up to set email alerts
|

Reorganizing pediatric rehabilitation services to improve accessibility: do we sacrifice quality?

Abstract: BackgroundThe impact of a pediatric rehabilitation service delivery reorganization to improve access to services on parents' and service providers' perception of service quality was evaluated. Child-, family-, service- and service provider-related characteristics possibly associated with these perceptions were explored.MethodsPerceptions were measured using the Measure of Processes of Care tools and open ended questions before (2007), during (2008) and following (2009) service reorganization. Child and family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 31 publications
0
37
1
3
Order By: Relevance
“…First, the SWOT provided a clear portrait of the program's situation overtime and results showed that after the implementation of the model, clinicians felt an increase in service accessibility but worried about the possibility of not being able to tailor services according to children's needs (Camden, Swaine, Tétreault, & Carrière., 2011). Families' and clinicians' perceptions of the service quality measured by the MPOC indicated that despite the upheavals caused by the reorganization of services, the quality was maintained during the 3 years (Camden, Swaine, Tétreault, & Brodeur, 2010).…”
Section: Evaluation and Continuous Quality Improvementmentioning
confidence: 94%
See 1 more Smart Citation
“…First, the SWOT provided a clear portrait of the program's situation overtime and results showed that after the implementation of the model, clinicians felt an increase in service accessibility but worried about the possibility of not being able to tailor services according to children's needs (Camden, Swaine, Tétreault, & Carrière., 2011). Families' and clinicians' perceptions of the service quality measured by the MPOC indicated that despite the upheavals caused by the reorganization of services, the quality was maintained during the 3 years (Camden, Swaine, Tétreault, & Brodeur, 2010).…”
Section: Evaluation and Continuous Quality Improvementmentioning
confidence: 94%
“…However, few models of rehabilitation service delivery are published; articles relate only to one health profession or to general models offering limited guidelines for service organization in pédiatrie rehabilitation. Others propose strategies (e.g., 30 min sessions rather than 60 min, changes in administrative procedures and increased group interventions) to reduce waiting times for children with disabilities (Clow et al, 2002;Miller et al, 2008), but these are more punctual solutions rather than global service reorganization strategies.…”
Section: Models and Evidence To Guide The Service Reorganization Processmentioning
confidence: 97%
“…Specifically for children with DCD, wait-times decreased following implementation from 214 days in 2007 to 63 in 2009, and the overall number of hours of services provided to each child (p=0.93) and the perception of service quality (p>0.15) remained stable over time (sub analysis reported in Camden et al, 2010). Parents of children with DCD reported appreciating 9 group interventions and the opportunities provided for their child to make friends and to learn new skills, even though some would have preferred access to more individual interventions (Camden et al, 2012).…”
Section: The Apollo Service Delivery Modelmentioning
confidence: 99%
“…Following implementation, the impact of the Apollo service delivery model on families of children with different diagnoses was evaluated and results revealed that service quality was maintained while the numbers of children receiving service increased and wait times decreased (Camden et al, 2010;Camden et al, 2013b) for all children in the Center, including children with DCD. Specifically for children with DCD, wait-times decreased following implementation from 214 days in 2007 to 63 in 2009, and the overall number of hours of services provided to each child (p=0.93) and the perception of service quality (p>0.15) remained stable over time (sub analysis reported in Camden et al, 2010).…”
Section: The Apollo Service Delivery Modelmentioning
confidence: 99%
See 1 more Smart Citation